ANALISIS SISTEM INFORMASI AKUNTANSI PERSEDIAAN OBAT-OBATAN PADA RUMAH SAKIT AR BUNDA LUBUKLINGGAU - Aulia Tri Rizky; Dewi Anggraini; Yuli Nurhayati (LPPM Universitas Bina Insan, 2020)
The hospital operational activities, medical supplies have the most frequent usage. To support medical supplies management that is effective and efficient, the management needs accounting information system of inventory that is more actual and adequate. The purpose of this research is to found accounting information system of inventory in AR Bunda Hospital. This method of research is a qualitative study by using descriptive approach. The sources of the data are primary data and secondary data. There are three ways in technique for collecting the data, namely observation, interview, and documentation. The result of the study found that accounting information system of inventory in AR Bunda Hospital are going well, but the are some weakness such as medical supplies procedure, multiply task head of pharmacy installation, the lack of some documents/form and the accounting records to support accounting informaton system of inventory.